Flavian poetry - Nauta, Ruurd R.; Dam, Harm-Jan van, 1948-; Smolenaars, Johannes Jacobus Louis. (Mnemosyne, Supplements, 2006)
The reign of the Flavian emperors (69-96) saw the production of a large and varied body of Latin poetry: the epics of Valerius Flaccus, Silius Italicus and Statius, the Silvae of the same Statius, and the Epigrams of Martial. This poetry, long seen as derivative or decadent, is now increasingly appreciated for the daring originality of its responses both to the Latin literary tradition and to the contemporary Roman world. In the summer of 2003, the first-ever international conference on Flavian poetry, was held at Groningen, The Netherlands, bringing together leading scholars in the field from Europe, North America and Australasia. This volume offers a selection of the papers delivered on that occasion.